GENETIC VARIABILITY STUDIES IN PIGEONPEA [Cajanus cajan (L.) Millsp.] - JAKE LEE GALIAN, NIDHI MOHAN, C.V. SAMEER KUMAR; P. MALLESH (The Journal of Research ANGRAU, 2015)
Thirty-nine pigeonpea genotypes were evaluated for variability, heritability and genetic advance under rainfed condition during Kharif 2015 at International Crop Research Institute for Semi-Arid Tropics (ICRISAT). The analysis of variance showed significant differences among the genotypes for all the characters studied, indicating that there was high variability among the genotypes. Grain yield (t ha-1) has exhibited high genotypic and phenotypic coefficient of variation, thus indicates that this character is governed by genetic factors and possible improvement through selection. Whereas, plant height, number of primary branches plant-1, number of secondary branches plant-1, number of pods plant-1 and 100-seed weight obtained moderate estimates at both levels. This may imply that there is a scope of improvement in these characters. High heritability combined with high genetic advance as percent of mean was obtained for characters viz., days to 50% flowering, plant height, number of primary branches plant-1, number of secondary branches plant-1, no. of pods plant-1, 100-seed weight and grain yield (t ha-1). This indicates that the heritability was due to additive gene effects and selection would be promising for these characters